2017
DOI: 10.4103/ijem.ijem_536_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-Fluorocholine positron emission tomography/computed tomography and four-dimensional computed tomography in the preoperative localization of parathyroid adenomas-initial results

Abstract: Objective:We aimed to compare the diagnostic accuracy of 18F-Fluorocholine (FCH)-positron emission tomography/computed tomography (PET/CT) and four-dimensional (4D)- CT in detection and localization of eutopic and ectopic parathyroid adenoma (PA) in patients with hyperparathyroidism.Materials and Methods:Five patients with primary hyperparathyroidism underwent FCH-PET/CT after 60 min of 185 MBq of intravenous 18F-FCH administration. Images were acquired from head to mediastinum at 3 min per bed position. No in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Although the performance of CT is good, the main disadvantage is the higher radiation dose [24]. A pilot study demonstrated that FCH PET/CT is comparable in performance to 4D-CT [25], a recent study showed that the combination of FCH PET with 4D-CT was of added value [18], and a third study concluded that 4D-CT appears as a confirmatory imaging modality [19]. Furthermore, an interesting development is the use of FCH PET/MRI, with the reduction of radiation dose and increased soft-tissue resolution [16, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the performance of CT is good, the main disadvantage is the higher radiation dose [24]. A pilot study demonstrated that FCH PET/CT is comparable in performance to 4D-CT [25], a recent study showed that the combination of FCH PET with 4D-CT was of added value [18], and a third study concluded that 4D-CT appears as a confirmatory imaging modality [19]. Furthermore, an interesting development is the use of FCH PET/MRI, with the reduction of radiation dose and increased soft-tissue resolution [16, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Four-dimensional contrast-enhanced computed tomography (4D-CT) and 18 F-Fluorocholine positron emission tomography/computed tomography ( 18 F-FCH PET/CT) appear as two valuable second-line imaging options, superior to 99m Tc-sestamibi scintigraphy and neck US [ 13 , 14 , 15 , 16 ]. Regarding their relative diagnostic performances, comparisons between 18 F-FCH PET/CT and 4D-CT have been performed rarely and in a very small number of patients [ 17 , 18 ]. Therefore, no strong evidence exists to give preference to 18 F-FCH PET/CT over 4D-CT in clinical settings, and the choice of second-line pre-operative investigation is often based on both technical availability and local expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Recent patient level studies have shown good accuracy and equal or even superior detection using 18F-fluorocholine-PET/CT (FCH-PET/CT) compared to commonly used imaging using 99m Tc-sestamibi scintigraphy, ultrasound, and four-dimensional computed tomography ( 21 24 ). In this study, we therefore evaluated the sensitivity and specificity of FCH-PET/CT for preoperative localization in patients with pHPT and negative or equivocal 99m Tc-sestamibi scintigraphy and/or ultrasound.…”
Section: Introductionmentioning
confidence: 99%